A Review of Employer-Caused Delay Factors in Traditional and Building Information Modeling (BIM)-Enabled Projects: Research Framework. (23rd April 2021) - Barqawi, Mohammad; Chong, Heap-Yih; Jonescu, Emil
Abstract : Construction delays are considered a common worldwide problem. Previous studies have investigated construction delay factors from the perspectives of different project stakeholders. However, a thorough analysis of such delays on different types of construction projects in different geographies is still lacking, precisely the effect of employers' delays in traditional and building information modeling (BIM)-enabled projects. This research proposes a research framework to address potential employer-caused delay factors in traditional and BIM-enabled projects. A cross-sectional literature search was carried out to review construction delay factors and employer-caused delay factors in traditional and BIM-enabled projects. The study found that: (a) a research gap exists in traditional construction delay studies in specific continents and project types as well as in BIM-enabled project studies, (b) delay aspects have not been addressed or have been partially addressed in previous studies, and (c) a relationship model between employer-caused delay factors and success factors can be developed by studying the effects of BIM barriers and implementation strategies. This paper is the first to present a comprehensive review on delay factors and tender a novel framework to address employer-caused delay factors in both traditional and BIM-enabled projects.